2010
DOI: 10.1016/j.gca.2010.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Surface complexation of Cu on birnessite (δ-MnO2): Controls on Cu in the deep ocean

Abstract: Hexagonal birnessite (d-MnO 2 ) is a close analogue to the dominant phase in hydrogenetic marine ferromanganese crusts and nodules. These deposits contain $0.25 wt.% Cu which is believed to be scavenged from the overlying water column where Cu concentrations are near 0.1 lg/L. Here, we measured the sorption of Cu on d-MnO 2 as a function of pH and surface loading. We characterized the nature of the Cu sorption complex at pH 4 and 8 using EXAFS spectroscopy and find that, at pH 4, Cu sorbs to birnessite by inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 38 publications
(51 reference statements)
5
72
0
Order By: Relevance
“…The adsorption of divalent metals at vacancy sites involves the coordination of the metal to the three surface oxygen atoms surrounding the vacancy site, thus forming a triple-corner-sharing (TCS) complex (Manceau et al, 2002(Manceau et al, , 2007b. In birnessite suspensions equilibrated with Cu at low pH values (pH ≈ 4.0), Cu-TCS complexes were inferred from the Cu-Mn interatomic distance of 3.39-3.43 Å obtained from fitting extended X-ray absorption fine structure (EXAFS) spectra (Manceau et al, 2002;Sherman and Peacock, 2010;Arai, 2011). The occurrence of up to 20% Cu-incorporation (Cu-INC) at high pH values (pH ≈ 8.0) was proposed by Sherman and Peacock (2010) based on the appearance of a peak near 2.9 Å in the Fourier-transformed EXAFS spectrum for δ-MnO 2 sample with a loading of 0.068 mol Cu mol −1 Mn.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The adsorption of divalent metals at vacancy sites involves the coordination of the metal to the three surface oxygen atoms surrounding the vacancy site, thus forming a triple-corner-sharing (TCS) complex (Manceau et al, 2002(Manceau et al, , 2007b. In birnessite suspensions equilibrated with Cu at low pH values (pH ≈ 4.0), Cu-TCS complexes were inferred from the Cu-Mn interatomic distance of 3.39-3.43 Å obtained from fitting extended X-ray absorption fine structure (EXAFS) spectra (Manceau et al, 2002;Sherman and Peacock, 2010;Arai, 2011). The occurrence of up to 20% Cu-incorporation (Cu-INC) at high pH values (pH ≈ 8.0) was proposed by Sherman and Peacock (2010) based on the appearance of a peak near 2.9 Å in the Fourier-transformed EXAFS spectrum for δ-MnO 2 sample with a loading of 0.068 mol Cu mol −1 Mn.…”
Section: Introductionmentioning
confidence: 99%
“…In birnessite suspensions equilibrated with Cu at low pH values (pH ≈ 4.0), Cu-TCS complexes were inferred from the Cu-Mn interatomic distance of 3.39-3.43 Å obtained from fitting extended X-ray absorption fine structure (EXAFS) spectra (Manceau et al, 2002;Sherman and Peacock, 2010;Arai, 2011). The occurrence of up to 20% Cu-incorporation (Cu-INC) at high pH values (pH ≈ 8.0) was proposed by Sherman and Peacock (2010) based on the appearance of a peak near 2.9 Å in the Fourier-transformed EXAFS spectrum for δ-MnO 2 sample with a loading of 0.068 mol Cu mol −1 Mn. However, in a recent density functional theory (DFT) study, Kwon et al (2013) demonstrated that the incorporation of Cu into a vacancy site strongly inhibits the JahnTeller distortion of Cu, destabilizing the Cu-INC species relative to the Cu-TCS species at any pH value.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A missing link in contemporary palaeoceanography may be the modelling of molecular and particle-scale interactions of isotopic tracers [97]. There are fundamental gaps in our theoretical and modelling understanding of the underlying thermodynamics that control the broad biogeochemical processes used in the palaeoceanographic community.…”
Section: (Iv) Suggested Ways Forwardmentioning
confidence: 99%